Effect of silicon doping on graphene/silicon Schottky photodiodes. (2020) - Luongo, Giuseppe; Grillo, Alessandro; Urban, Francesca; Giubileo, Filippo; Di Bartolomeo, Antonio
Abstract: We realize two graphene/Si devices with the same structure but on different Si type and characterize their current-voltage properties. We observe that the gr/n-Si junction has a higher Schottky barrier and rectification factor than the gr/p-Si junction. The low Schottky barrier of the gr/p-Si junction is explained by the p-doping of graphene, induced by polymethylmethacrylate residues and chemicals used for the transfer process, which align the graphene Fermi level to the Si valence band. Under illumination, both devices show a reverse current greater than the forward one. This phenomenon is attributed to the metal-oxidesemiconductor capacitor connected in parallel with the gr/Si Schottky junction. Although both junctions possess a high responsivity, the gr/p-Si junction shows a high dark current that hampers its use as photo detector.